Study to assess the patterns of hypertension and factors influencing hypertension in chronic kidney disease - Subramanya, Abhishek M.; Khan, Mohammed Fahad; Ravindra, Aditi (International Journal of Research in Medical Sciences, 2023)
Background: A large proportion of CKD patients have inadequate BP control, and the proportions vary from studies to studies. Clinic BP is considered insufficient to diagnose HTN and monitor overall BP control because it does not correlate well with ambulatory blood pressure monitoring (ABPM), which encompasses white-coat or masked HTN. CKD is associated not only with an abnormal dipping pattern but also with white-coat or masked HTN. Objective of this study was to evaluate the factors influencing the blood pressure in chronic kidney disease patients. Methods: A cross sectional study was conducted at a tertiary hospital in South India from 1st of January 2016 to 31st of July 2017. A total of 124 cases were included in the study. Results: Among subjects with controlled HTN, 31.4% were overweight and 5.7% were Obese. Among Stage 3 CKD subjects, 53.7% had controlled HTN, 12.2% had masked HTN, 12.2% had persistent HTN. We reported that among those with proteinuria 2+, 38.5% had controlled HTN, 11.5% had masked HTN, 19.2% had persistent HTN and 30.8% had white coat HTN. In the study among diabetics, 17.5% had controlled HTN, 36.8% had masked HTN, 43.9% had persistent HTN and 1.8% had white coat HTN. Conclusions: Stage of CKD, diabetes mellitus and proteinuria are determinants of hypertension in CKD patients. ABPM is the best method to monitor BP and hence in the proper management of HTN and in prevention of target organ damage in CKD patients.